AESTHETICS AND HYBRIDITIES IN SONGS "YADA YADA" AND "I AM VIRUS" INSIDIOUSLY CLAIMING INCLUSIVITY IN INDIGENOUS PEOPLES’ MUSIC - Chowdhury, Shib Shankar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of this research paper is to study the revival of divine music on screen to become part of inclusivity in Indigenous Peoples’ Music and Dance music. For this analysis, I have taken into consideration my own two different songs belonging to the mix genre of world and pop music: “Yada Yada” produced in Mumbai and London, and “I am Virus” produced in Brisbane. An encrypted secret of divinity belonging to indigenous Indians is shown, indicating the potential end of civilization through the present scenario of war and crisis if not understood. This may be relegated by orientalists to make it a part of inclusivity in indigenous music. The music video of “Yada Yada” persuasively is crucial for making visual aids relics for the awareness of the audience or consumers. Lyrics of the song are mostly written in English, with one verse in Sanskrit borrowed from the Indian indigenous epic Mahabharata. In this music video, sound effects and video are incorporated to add dimension to dramatize the video’s plot, improving the viewer’s experience. In contrast, the record “I am Virus” and its music video, being anthropomorphic in nature, present an unadulterated object of hybridity opposing ideas of purity and authenticity of origins. This approach opposes authoritarianism and racialism, contributing to a pluralistic culture. This adds weight to Indigenous Peoples’ Music.